PENGARUH NILAI-NILAI KEIMANAN ISLAM DI DESA NAMAN, KECAMATAN NAMAN TERAN, KABUPATEN KARO - Sinulingga, Aldi Alfarel; Syahputra, Heru; Harahap, Salahuddin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to explore and analyze the influence of Islamic akidah (creed) values on various aspects of community life in Naman Village, Naman Teran District, Karo Regency. Islamic akidah, as the foundation of faith, not only shapes individual religious practices but also influences social interactions, economy, and education. Using a qualitative approach, this research examines how akidah values such as honesty, justice, mutual cooperation (gotong royong), and responsibility are reflected in the daily lives of Naman Village residents, who are predominantly Protestant Christians but live in harmony with the Muslim minority. The findings indicate that Islamic akidah promotes consistency in worship, fosters noble character, strengthens social bonds through mutual cooperation, and encourages ethical economic practices. Despite facing challenges such as differing religious understandings and the impact of modernization, opportunities to strengthen aqidah remain through the active role of religious leaders, formal and informal education, utilization of technology, and support from local government and institutions. This study provides a clear picture of the relationship between Islamic akidah and social practices at the village level, contributing to the development of socio-religious studies in Indonesia.